Development of an evaluation programme for the intelligent management of mobile infectious disease hospitals in response to public health emergencies: a Delphi study - Xu Luo; Juanling He; Sifeng Wu; Rongrong Ni (BMJ Open)
Objectives To construct a scientific and practical intelligent management assessment programme for mobile infectious disease hospitals and explore pathways to enhance their management effectiveness.Design A preliminary pool of indicators was developed based on policy documents issued by the Chinese government. Two rounds of Delphi expert consultations were conducted via email between February and August 2024. These indicators were then refined using the margin method. Finally, a hierarchical analysis was employed to assign weights to each indicator.Setting and participants In line with the policy guidance of the Chinese government, an initial set of assessment indicators for smart management of mobile infectious disease hospitals was established. 32 experts with extensive knowledge in the construction of smart management systems for such hospitals were chosen to participate in the Delphi study, offering a comprehensive professional perspective.Results The Cr values were 0.860 (Round 1) and 0.894 (Round 2), demonstrating the accuracy and reliability of the expert consultations. The coordination coefficient among the experts was statistically significant at the p<0.01 level, reflecting a high degree of consensus. In total, 29 assessment items for the smart management of mobile infectious disease hospitals were finalised.Conclusions A comprehensive set of indicators for assessing smart management in mobile infectious disease hospitals has been developed. This system is scientific, logical and dependable, providing effective guidance for the smart development of such hospitals. It not only improves the quality and efficiency of medical services but also safeguards patients’ health rights.